QUALITY TOOL: a study of its applicability in a metallurgical company - Silva, Luana de Siqueira; de Campos, Ronaldo Ribeiro (Revista Interface Tecnológica, 2022)
The present work presents the tools of qualities and how to use them in a common problem within a company, regardless of its size or the environment in which it is found, there is a need to seek competitiveness. This work will be applied to a routine practice within a company in the metallurgical branch, focusing on agricultural equipment and machinery for soil preparation and cultivation, and aims to facilitate the understanding of employees in the execution of their routine services and assist them in solving of problems. The work consists of a qualitative research in websites, articles and books and an exploratory research in the studied company, presenting its results on the importance of the concept of quality introduced in the process.
Keywords: Industry; Tools; Management; Quality